ALIEN PLANT SPECIES IN GIURGIU COUNTY, ROMANIA: AN INVENTORY AND DISTRIBUTION ANALYSIS (Acta Horti Botanici Bucurestiensis, 2024)
Giurgiu County, a crucial hub in the Pan-European Corridor with the sole Danube bridge to Bulgaria, plays an important role in  potential pathways for introducing alien plant species. However, the information regarding the distribution of alien plants in this county is incomplete. Our study aims to address this gap by providing a comprehensive analysis of the current distribution of alien  plant species based on field records collected from September 2019 to November 2022. Following the guidelines of the POIM/178/4/1/120008 project, data were collected across diverse habitats. Our findings reveal 89 alien plant taxa, including 58 newly reported at the county level. Over half of the alien plant species (66.29%) are also present in the natural protected areas. The study contributes essential information for biodiversity conservation, emphasizing ongoing monitoring and invasive species management  within Giurgiu County's protected areas.